Thermal acclimation and adaptation across populations in a broadly distributed soil arthropod. (10th February 2019) - Jensen, Anne; Alemu, Tibebu; Alemneh, Temesgen; Pertoldi, Cino; Bahrndorff, Simon
Abstract: The relative contributions of phenotypic plasticity and adaptive evolution to the responses of species to climate change are poorly understood. It has been suggested that some species or populations will have to rely on their ability to adjust their phenotype rather than on adaptation through evolutionary adaptation. We test the extent of intra‐ and inter‐population patterns of acclimation and genetic variation in multiple traits directly related to environmental tolerance limits in the broadly distributed soil dwelling collembolan Orchesella cincta . Genetic variation in both dynamic and static assays of thermal tolerance was present across seven populations spanning 14° of latitude and both heat and cold tolerance were significantly correlated with latitude. Short‐term heat and cold acclimation significantly increased thermal tolerance limits across all populations, and there was local adaptation for acclimation responses for some traits. Furthermore, results showed large acclimatization responses in the field within populations for cold tolerance throughout a 13‐month period and smaller acclimatization responses for heat tolerance. Acclimatization responses were correlated with microhabitat temperature at the site of collection suggesting that plastic responses are highly dynamic and allow organisms to cope with changes in temperature. Our findings demonstrate small differences in upper and lower thermal tolerance limits across populations, but substantial local acclimatization effects dictated by microhabitat temperatures, and also highlight strong tradeoffs and limited scope to respond to increasing temperatures. These findings demonstrate the need for incorporating information on species' ability to respond to environmental change using both laboratory and field approaches into climate change models. Aplain language summary is available for this article. Abstract : Plain Language Summary